Praktik Pinjam Meminjam Bersyarat Di Desa Adian Jior - Erna Dewi, Khairul Bahri Nasution, Nur Hasimah (Islamic Circle, 2022)
The practice of borrowing, both in the form of money and gold, has often occurred, even most of the people require the provision of rice fields as collateral for the loan by the lender. As happened in Ajian Jior village, people in Adian Jior Village, Panyabungan District, practiced borrowing both in the form of money and gold by requiring the provision of rice fields as collateral for the loan. When someone borrows gold or money, they will give their rice fields as collateral from the debt with a time limit of two harvests or 1-2 years or according to the agreed time. During the loan and loan, the paddy field is under the power of the lender and he has the right to manage and benefit from the paddy field. And everything related to the rice field is within the power of the lender. This research is included in the field research category (Field Research), this research is descriptive using a qualitative approach, because the problems in this study are by examining social symptoms that occur in society. The results obtained are based on the researcher's analysis that the practice of conditional borrowing that occurred in Adian Jior Village was invalidated due to conditions that were contrary to Islamic laws. And the practice of borrowing enters into usury because of the addition of the loan and the form of control over other people's property.